(untitled) (Fiep Bulletin - online, 2014)
The graduation in Physical Education traditionally traces to the graduation of teachers. However, due to the approval of educational rules, from 1996 to 2004 the Physical Education Courses had to build up a new curriculum for Bachelor’s Degrees, since nowadays the graduates can only work in schools. Taking into consideration the responsibility and complexity of building up a "new" curriculum due to the changes which have been happening in the work market, the aim of this paper is to contribute towards the professional formation debate through the analysis of the Bachelor’s Degree curriculum approved by the Resolution CNE/CES Nº 07/04 for colleges and universities in Vale do Rio dos Sinos and Porto Alegre/RS. Among the 8 courses that offer a degree in Physical Education, 5 already offer Bachelor’s Degrees. On the one hand, considering only the subjects that are taught and the fact that the new curricula have just been introduced and the proper adjustments are being made, we can conclude that most kept the tradition in Physical Education with practical and technical secluded subjects distributed in the curriculum. On the other hand, there are few social philosophical subjects (basically 3). But it can be seen as advancement because they relate to the Physical Education field. Health is restricted to gym, weight lifting and biological subjects and only few courses bring innovation to the subjects they offer.